Lid technique을 활용하여 치근단 수술에서 역충전을 시행한 증례 보고 - 이윤주(Yoon-Joo Lee); 조경모(Kyung-Mo Cho); 박세희(Se-Hee Park); 이윤(Yoon Lee); 김진우(Jin-Woo Kim) (Journal of dental rehabilitation and applied science, 2023)
Apical sealing with proper retrograde filling material and technique is the key factor for successful apical surgery. In order to provide impeccable apical sealing and healing, various mechanical and chemical characteristics of retrograde filling material is required. MTA has been used as the gold standard of retrograde filling due to its unprecedented advantages. As MTA has long setting time and difficult handling properties, premixed putty type bioceramic material has been newly developed. For efficient retrofilling with premixed putty type biocreamic material, 'Lid technique' was also proposed. The following cases present apical surgery using newly developed premixed putty type bioceramic material with Lid technique. 치근단 수술의 성공 여부는 적절한 역충전 재료와 충전 기법을 선택하여 근단부를 밀폐하는 데 달려있다. 역충전 재료는 확실한 밀폐를 제공하고 양호한 치유를 얻기 위하여 여러가지 물리화학적 특성들이 요구되는데 현재까지 MTA는 기존의 재료들이 가지지 못한 전례없는 우수한 장점을 갖추어 역충전 재료의 gold standard로써 사용되어 왔다. 그러나 이러한 MTA도 경화시간이 길고 조작이 어렵다는 단점이 있어 최근에는 이러한 단점을 개선한 premixed putty type bioceramic material이 개발되었다. 또한 이러한 재료를 활용하여 역충전 와동을 효율적으로 충전하기 위한 'Lid technique'이 함께 제안되었다. 본 증례 보고는 치근단 수술에서 premixed putty type material과 Lid technique을 활용한 증례에 대하여 소개하고자 한다.